QUALITY STANDARDS FOR DISTANCE LEARNING IN HIGHER EDUCATION: A COMPARATIVE ANALYSIS OF CANADIAN AND RUSSIAN PRACTICES - Natalia V. Buhanova; Konstantin V. Kuz’min; Larisa E. Petrova; Sergey A. Chemezov (Образование и наука)
The aim of the investigation is to perform comparative analysis of the quality assessment and policies of quality assurance in postsecondary education in Canada and Russian Federation.Methods. The theoretical methods involve comparative analysis and synthesis, induction and deduction, extrapolation and modelling.Results. Russia and Canada have different policies on quality assurance in the distance learning and are at different stages of implementation of distance learning into postsecondary curricula. The Canadian system of postsecondary education is regulated not by the State but by professional societies, licensing organisations, and experts. Canadian postsecondary institutions have efficient systems of quality assurance, quality standards and accreditation. Blended learning is widely used in Canadian medical schools and is mandatory for continuous professional development. In Russia, the system of quality assurance for distance learning is regulated by the State. At present, Russia has developed policies on distance learning but unified quality standards in this field are absent. Blended learning is used in the medical schools but its implementation has just begun as continuous professional development.Scientific novelty. For the first time, the results of comparative analysis of the policies on quality assurance in distance learning in Russia and Canada are described.Practical significance. This research has showed the needs of the development of the system of quality standards and the policy on quality assurance of distance learning in the Russia postsecondary education.